A New Approach for Quantitative Surface‐Enhanced Raman Spectroscopy through the Kinetics of Chemisorption. Issue 3 (25th January 2021) - Wen, Bao‐Ying; Wang, An; Lin, Jia‐Sheng; Guan, Peng‐Cheng; Radjenovic, Petar M.; Zhang, Yue‐Jiao; Tian, Zhong‐Qun; Li, Jian‐Feng
Abstract: Surface enhanced Raman spectroscopy (SERS) is a non‐destructive, highly sensitive, and rapid analytical tool, which has been widely used in different fields, especially for trace quantities of analyte. However, using SERS for reliable quantitative sample analysis is still a great challenge. Herein, a new approach to quantitative SERS analysis at nanostructured substrates that does not require an internal standard or well‐ordered nanostructured SERS substrates is developed. This method is based on the kinetics of chemisorption, that is, on a homogeneous surface, the time taken for adsorption of an adsorbate (adenine or melamine) to reach equilibrium negatively correlates with the concentration of the adsorbate. Quantitative analysis is achieved by using in situ SERS to acquire the adsorption profile of the adsorbate and enabling the adsorption equilibrium time to be calculated. There is excellent correlation between the adenine and melamine SERS response over adsorption equilibrium time with concentration, and the correlation coefficients are 0.9906 and 0.9682, respectively. Moreover, milk sample spiked with the melamine is also studied, and the standard recovery rate is 106%. This work demonstrates a novel, non‐destructive, and cost‐effective quantitative SERS detection technique, which can broaden applications across multiple fields. Abstract : A new method for SERS quantitative analysis based on chemical adsorption kinetics is established, which does not need an internal standard or well‐ordered substrate. Meanwhile, this approach is also compared with the standard method of trace milk detection, and the good correlation is obtained, which expands the application of SERS technology in food safety fields.